Assessment of the environmental impact of urban wastewater and the treatment capacity of the Saida activated sludge plant (North-western Algeria) on the occasion of Eid Al-Adha - Zairi, Souad; Meddah, Boumediene; Slimani, Miloud; Rahmani, Asmaa (Vojnotehnički glasnik / Military Technical Courier, 2025)
Introduction/purpose: The slaughter of livestock during Eid Al-Adha generates significant quantities of wastewater rich in organic pollutants. However, the specific impact of these effluents on water quality remains poorly documented. This study aimed to assess the pollutant loads discharged into the Saida Valley during Eid Al-Adha and evaluate the treatment capacity of the local activated sludge wastewater treatment plant (WWTP). Methods: Water samples were collected from different points in the sewerage system at various times throughout the day during three Eid Al-Adha events (2017, 2018, and 2019). Several physico-chemical parameters were analyzed, including temperature, pH, electrical conductivity, chemical oxygen demand (COD), five-day biochemical oxygen demand (BOD₅), total suspended solids (TSS), ammonium, nitrates, nitrites, and phosphorus. The measured pollution levels were compared to the Algerian regulatory standards to assess compliance. Results: The analyses revealed a sharp increase in pollution levels in the morning, followed by a gradual decline in the evening. High pollutant loads from slaughter effluents significantly degraded the water quality of the Saïda River. The organic pollution index classified these discharges as very high pollution. The excessive input of organic matter and nutrients resulted in oxygen depletion and eutrophication risks. Conclusion: The discharge of untreated slaughter wastewater poses serious environmental and public health risks. Strengthening wastewater management strategies during Eid Al-Adha, enhancing treatment processes at the Saïda WWTP, and enforcing strict environmental regulations are essential to mitigating these impacts.